ÀWỌN `ỌNÀ MÍMỌ́: os caminhos sagrados das mulheres do Axé em Nova Iorque (EUA) - Niel, Marcelo [UNIFESP] (2017)
This doctoral research is an ethnography about the migration of Candomblé (an Afro-Brazilian religion) to the city of New York in the United States of America. I describe the trip of three Brazilian “mães de santo” (“mothers of saint”) who carry their practices and knowledge from Brazil. I report their establishment in the city, the dialogue with the urban space in a megalopolis, the changes occurred in their rituals and their possible translations in this new space, the clientele and their motivations. The first article, “Àwọn `Ọnà Mímọ́: the sacred ways of the Axé Women in New York”, observe and analyze the itinerary of Brazilian mães de santo (“mothers of saint”) who traveled to New York City carrying the knowledge and the practices of Candomblé with them. It also seeks to analyze how this itinerary promotes the establishment and permanence of Candomblé in Brazil and abroad. The text is based on an ethnographic research carried out between 2013 and 2017, through participating observation and monitoring of the everyday life of these mães de santo (“mothers of saint”). It was possible to learn that Candomblé is founded on an open, dynamic religious codex, and that the constant movement through which it reinvents itself and renegotiates its practices is at the very core of its existence. The second article, “Àwọn Ìyá Awo: the ladies of secretin the Big Apple: women and Candomblé practices in New York City, USA”, the presence of three Brazilian mães de santo (“mothers of saint”) stood out. They have been led to rethink their practices in the context of life in the USA and to reshape standard religious configurations—in short, they have created new traditions, as per Roy Wagner’s academic work (1975). By telling the stories of these women, it was possible to reveal the mechanisms through which they have reinvented their religion: articulating secrets, permissions and transpositions related to their practices while also (and rather paradoxically) contributing to preserve the original essence of Candomblé. And by doing that, they have also helped spread and establish their religion in a foreign country. One of the most important aspects of the reinvention process concerns the so-called hierarchical changes; in New York, the relationship between the mães de santo and the practitioners is more horizontal than then one observed on the terreiros located in Brazil. The third and last article, “Oogun Àṣẹ: Candomblé practices and health care in New York City, USA”, presents the results of an ethnography carried out between 2013 and 2017, which relied on participating observation, interviews and monitoring of the everyday life of three Brazilian mães de santo (“mothers of saint”) who sought to reinvent Candomblé in New York City, USA. The article follows them as they attempt to transpose their religious beliefs and practices to this new, foreign context. It describes their relationship with practitioners who seek health care through the use of plants and prayers during religious rituals and ceremonies.